Multifunctional reconfigurable wilkinson power divider with single pole double throw switch for rf front-end communications - Edward, Nurhasniza (2022)
Current and future communication systems necessitate reconfigurable structures and extended features, which are taken into account in the development of microwave devices such as: filters, antennas, and amplifiers. Reconfigurability refers to the ability to adjust or control a power divider's features dynamically while still maintaining acceptable overall performance. Power divider with adjustable power division ratio, center frequency, and transmission mode or function selectivity are the key features targeted by reconfigurable power dividers. Commonly, PIN diodes and varactors are used to achieve reconfigurability. One type of reconfigurable power divider that has recently gained popularity is switchable power dividers, in which the structure of the power divider can be adjusted to achieve different functionality. There are many techniques have been developed to achieve reconfigurable power divider, but majorities of the reconfigurable designs are focused on a single element, either on a power divider or single pole double throw (SPDT) switch. Therefore, the aim of this research is to design novel structure of reconfigurable modified Wilkinson power divider with SPDT switch function which promises a new potential functionality of the microwave devices. Two designs approaches were introduced, which are reconfigurable modified WPD and reconfigurable function modified WPD using Roger Duroid RO4350B with a dielectric constant of 3.48. To realize the concept, the techniques used in designing the reconfigurable modified WPD and reconfigurable function modified WPD have been combined to form a single structure of a novel reconfigurable modified WPD with SPDT switch function. To validate the design technique, mathematical analysis of the reconfigurable modified WPD as a SPDT switch is presented to prove the switchable mechanism. The commercial software program that has been used in the design and development of the main designs is the Advanced Design System (ADS) software. All designs were simulated, manufactured, and measured. The proposed design’s total layout is 48.1 mm x 80.9 mm. The simulation results showed good agreement for both functions and frequencies, with S11 less than -15 dB, S21 more than -4.2 dB, and S23 less than -10 dB. The experimental results show good agreement with the simulated results. Even though there was a frequency shift in the measurement, the measurement results still correlated with the simulation results. The benefits of the reconfigurable integrated design are potentially reducing the entire structure's size, easy to fabricate and cost effective. The outcomes of the proposed reconfigurable integrated design may facilitate improvements in an integrated technique for RF front end systems.